Congenital Hypotrichosis Simplex: A Case Report (Bangladesh Journal of Child Health, 2019)
Congenital hypotrichosis simplex of scalp is a rare disorder which only affect the scalp hair. Rest of the hair bearing areas are spared. In this disorder the scalp hair are absent or sparse. We describe a 5 month old boy presented with no growth of scalp hair since birth in this case report. After taking detailed history, a thorough physical examination was done. Other causes of alopecia were ruled out and finally the child was diagnosed as a case of Congenital Hypotrichosis Simplex (CHS).Bangladesh J Child Health 2019; VOL 43 (1) :59-61